PENGARUH MEDIA FLASHCARD BERBASIS AUGMENTED REALITY TERHADAP KEMAMPUAN MEMBACA FUNGSIONAL ANAK TUNAGRAHITA SEDANG - Puspita, Agnes; Asmiati, Neti; Maslahah, Sayidatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Functional reading ability is an essential skill that supports the independence of students with moderate intellectual disabilities in daily life. However, cognitive limitations and the low attractiveness of instructional media often hinder the learning process of reading skills. This study aimed to analyze the effect of augmented reality–based flashcard media on the functional reading ability of students with moderate intellectual disabilities. This study employed a quantitative approach using a quasi-experimental pretest–posttest design. The research subjects consisted of three students with moderate intellectual disabilities. The instrument used was a functional reading ability test. Data were analyzed using the Wilcoxon test to examine differences in reading ability before and after the use of the media. The results indicated that the use of augmented reality–based flashcard media showed a positive effect on improving functional reading ability among students with moderate intellectual disabilities. These findings suggest that the integration of augmented reality technology into visual learning media can enhance students’ understanding and learning motivation. Therefore, augmented reality–based flashcard media shows potential as an alternative instructional medium to support functional reading learning for students with moderate intellectual disabilities.